2008
DOI: 10.1016/j.jembe.2008.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope signatures reveal that diet is related to the relative sizes of the gills and palps in bivalves

Abstract: Carbon isotope signatures reveal that diet is related to the relative sizes of the gills and palps in bivalves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 68 publications
(78 reference statements)
1
12
1
2
Order By: Relevance
“…This is also evident from the lack of significant relationship between the δ 13 C values for muscle and age or size because of the small variability in the δ 13 C isotopic values. These results however are not supported by previous dietary studies using bivalves [31,32], where carbon isotope ratios showed greater differences than nitrogen isotope ratios. The large differences in δ 15 N between young and adult scallops may suggest that they preferred different food sources but to some extent, scallops still occupied the same trophic position (2.3-2.7).…”
Section: Resultscontrasting
confidence: 99%
“…This is also evident from the lack of significant relationship between the δ 13 C values for muscle and age or size because of the small variability in the δ 13 C isotopic values. These results however are not supported by previous dietary studies using bivalves [31,32], where carbon isotope ratios showed greater differences than nitrogen isotope ratios. The large differences in δ 15 N between young and adult scallops may suggest that they preferred different food sources but to some extent, scallops still occupied the same trophic position (2.3-2.7).…”
Section: Resultscontrasting
confidence: 99%
“…These are (1) three guilds of grazers (chitons; limpet‐like gastropods including haliotids and patellogastropods; and coiled trochoidean and littorinid gastropods); (2) ten guilds of suspension‐feeders (byssally attached epifaunal mytilid mussels; oysters and oyster‐like cemented bivalves; pectinid scallops; nonsiphonate shallow‐burrowing bivalves in Arcoida and Crassatelloidea; siphonate shallow‐burrowing veneroidean bivalves; active shallow‐burrowing cardiid bivalves; shallow‐burrowing active mactrid bivalves; deep‐burrowing mactrid and myoidean bivalves; epifaunal calyptraeid slipper limpets; and high‐spired epifaunal to shallowly burrowing turritellid gastropods); (3) deposit‐feeders (tellinoidean bivalves); (4) chemosymbiotic bivalves (lucinids and thyasirids); and (5) four guilds of predators (drilling soft‐bottom naticids; drilling muricids, mainly on hard bottoms; shell‐wedging and generalized predatory buccinoidean whelks; and shell‐enveloping volutids). These trophic guilds incorporate considerable variation: most large grazers have broad diets that often include sessile animals, as well as primary producers (Otaíza & Santelices, 1985; Briscoe & Sebens, 1988; Camus, Daroch & Opazo, 2008; Sanhueza et al ., 2008; Aguilera, 2011); and suspension‐feeders take up dissolved organic matter and food particles from the sediment in addition to particulate food suspended in water (Compton et al ., 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This can be related to the different feeding behaviors of the two species, which has been used to explain natural δ 13 C differences between suspension and deposit feeding bivalves (Crompton et al, 2008). M. moesta is a benthic suspension and surface-deposit feeder, utilizing the top surface layer of the sediments upon which algal food (i.e., experimental enriched food source) settles (McCormick-Ray et al, 2011;Sirenko and Gagaev, 2007;own observations).…”
Section: Species-specific Isotopic Tracer Assimilationmentioning
confidence: 99%